2014
DOI: 10.1074/jbc.m113.536391
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Nuclear and Synaptic Shuttling of Afadin Promotes Spine Plasticity and Histone Modifications

Abstract: Background: Coordinated synaptic and nuclear signaling is required for long lasting changes in neuronal morphology. Results: Afadin undergoes activity-dependent bi-directional shuttling to synapses and the nucleus resulting in dendritic spine remodeling and histone modifications. Conclusion: Afadin is required for coordinated signaling at synapses and the nucleus. Significance: Bi-directional trafficking of afadin is required for coordinated synaptic and nuclear signaling in response to activity-dependent stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…Intriguingly, we found that AF6 represses Snail expression depending on AF6's nuclear localization in PC cells. A similar phenomenon of AF6 nuclear localization also was observed when cells were exposed to growth factor signalling, and nuclear localization of AF6 may facilitate the induction of a transcriptional programme 14,[24][25][26] . However, there exists little evidence to show that AF6 can play a role as a transcriptional co-factor.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Intriguingly, we found that AF6 represses Snail expression depending on AF6's nuclear localization in PC cells. A similar phenomenon of AF6 nuclear localization also was observed when cells were exposed to growth factor signalling, and nuclear localization of AF6 may facilitate the induction of a transcriptional programme 14,[24][25][26] . However, there exists little evidence to show that AF6 can play a role as a transcriptional co-factor.…”
Section: Discussionsupporting
confidence: 52%
“…Accumulating evidence suggests that AF6 is a dual-residency protein, and its nuclear localization and transcriptional repressor activity are closely correlated 14,[24][25][26] . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that afadin is a dual residency protein present in both nuclear and cytosolic compartments, and specifically at synapses (Buchert et al, 2007;VanLeeuwen et al, 2014). Moreover, we have recently shown than activity-dependent signaling causes bi-directional trafficking of afadin to discrete nuclear and synaptic sites within the same cell (VanLeeuwen et al, 2014). As acute exposure to estradiol has been shown to also cause the enrichment of afadin at synapses , we reasoned that this may also cause afadin to traffic to the nucleus within the same cell.…”
Section: Acute Estradiol Treatment Causes Bi-directional Trafficking mentioning
confidence: 99%
“…The rapid post-translational modification of H3 has been observed in response to synaptic activity as well as neuromodulators (Brami-Cherrier et al, 2007;Stipanovich et al, 2008;Wittmann et al, 2009;VanLeeuwen et al, 2014). In particular, modulation of H3S10p by these stimuli, is thought to link extracellular signals with chromatin remodeling, and thus the regulation of genes associated with learning and memory (Riccio, 2010;Maze et al, 2013;Watson and Tsai, 2017).…”
Section: Estradiol Rapidly Incudes Phosphorylation Of Histone H3mentioning
confidence: 99%
See 1 more Smart Citation